Analisis Implementasi Kebijakan Sosial Pencegahan Stunting di Kabupaten Malang - Hutri Agustino; Eko Rizqi Purwo Widodo (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
This study aims to assess the level of achievement of the success of the policy program by examining the implementation of the Stunting Prevention Policy in Malang Regency based on Regent Regulation Number 33 of 2018. According to the statistics of the Malang Regency Health Office in 2018 which recorded that there were at least 30,323 stunted children, which were divided into two groups, namely very short and short based on classification with height measurement criteria. This study used a qualitative technique with a descriptive type, and the participants were selected purposively with program recipient informants from the Malang Regency area. The results showed that the Department of Population Control and Family Planning (DP2KB) of Malang Regency consisted of four areas, namely: (1) Field of Counseling and Mobilization of Regional Family Planning (PPKBD); (2) Population Control Sector; (3) Family Resilience and Welfare Sector; and (4) Family Planning Service Sector. Each of these four fields has a number of priority activity programs in preventing stunting in Malang Regency.